Empirical Evidenceon the Effects of Tax Incentives - Klemm, Alexander (IMF Working Papers; Working Paper, 2009)
This paper considers two empirical questions about tax incentives: (1) are incentives used as tools of tax competition and (2) how effective are incentives in attracting investment? To answer these, we prepared a new dataset of tax incentives in over 40 Latin American, Caribbean and African countries for the period 1985-2004. Using spatial econometrics techniques for panel data to answer the first question, we find evidence for strategic interaction in tax holidays, in addition to the well-known competition over the corporate income tax rate. We find no evidence, however, for competition over investment allowances and tax credits. Using dynamic panel data econometrics to answer the second question, we find evidence that lower corporate income tax rates and longer tax holidays are effective in attracting FDI, but not in boosting gross private fixed capital formation or growth.